Robert B. Parker's fallout [large type] - Parker, Robert B., 1932-2010; Lupica, Mike (Parker, Robert B., 1932-2010. Jesse Stone novels, 2022)
"The town of Paradise is devastated when a star high-school baseball player is found dead at the bottom of a bluff a day after winning the team's biggest game. For Jesse, the loss is doubly difficult--the teen was the nephew of his colleague, Suitcase Simpson, and Jesse had been coaching the young shortstop. As he searches for answers, he is stonewalled at every turn. Jesse suddenly must divide his attention between two cases after the murder of former Paradise police chief Charlie Farrell. The race to find answers is on. In the end, Jesse and his team must discover the common factor between the two deaths to prevent a third"--